2021
DOI: 10.1186/s12879-021-06053-3
|View full text |Cite
|
Sign up to set email alerts
|

Liver function following hepatitis C virus eradication by direct acting antivirals in patients with liver cirrhosis: data from the PITER cohort

Abstract: Background The development of direct-acting antivirals (DAA) for HCV has revolutionized the treatment of HCV, including its treatment in patients with HIV coinfection. The aim of this study was to compare the changes in liver function between coinfected and monoinfected patients with cirrhosis who achieved HCV eradication by DAA. Methods Patients with pre-treatment diagnosis of HCV liver cirrhosis, consecutively enrolled in the multicenter PITER co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Conversely, the patients with liver cirrhosis constituting the majority in the analyzed population are considered to be the most at risk of serious liver complications such as hepatic decompensation in the form of ascites and encephalopathy, the upper gastrointestinal bleeding as a consequence of portal hypertension, and hepatocellular carcinoma. We have shown that the overall and annual prevalence of these severe medical events was lower from the third year of follow-up than during the first 2 years, which means less risk of complications over time, and our findings supported the results of other studies [19][20][21][22][23][24][25]. However, none of these studies covered such a long period of 5 years follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, the patients with liver cirrhosis constituting the majority in the analyzed population are considered to be the most at risk of serious liver complications such as hepatic decompensation in the form of ascites and encephalopathy, the upper gastrointestinal bleeding as a consequence of portal hypertension, and hepatocellular carcinoma. We have shown that the overall and annual prevalence of these severe medical events was lower from the third year of follow-up than during the first 2 years, which means less risk of complications over time, and our findings supported the results of other studies [19][20][21][22][23][24][25]. However, none of these studies covered such a long period of 5 years follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…The continued appearance of older patients in the clinic also argues for an increase in efforts to target treatment and follow-up efforts since they may represent a cohort with the gradual evolution of the liver disease and at significant risk. This is especially important given the solid evidence that even patients with advanced liver disease benefit from treatment with respect to the progression of the disease [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of orally administered antivirals that are able to cure the HCV infection in more than 90% of treated patients represents a significant breakthrough in HCV therapy. However, most patients in low/medium-income countries have little access to diagnosis and treatment ( Quaranta et al, 2021 ). Prevention of the viral infection remains the most efficient way to reduce HBV/HCV-related morbidity and mortality.…”
Section: Plant-made Vaccines Against Viral Diseases In Humansmentioning
confidence: 99%